2020
DOI: 10.3389/fendo.2020.00117
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Propranolol on Bone, White Adipose Tissue, and Bone Marrow Adipose Tissue in Mice Housed at Room Temperature or Thermoneutral Temperature

Abstract: Growing female mice housed at room temperature (22 • C) weigh the same but differ in body composition compared to mice housed at thermoneutrality (32 • C). Specifically, mice housed at room temperature have lower levels of white adipose tissue (WAT). Additionally, bone marrow adipose tissue (bMAT) and cancellous bone volume fraction in distal femur metaphysis are lower in room temperature-housed mice. The metabolic changes induced by sub-thermoneutral housing are associated with lower leptin levels in serum an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 86 publications
1
25
0
Order By: Relevance
“…Adipose tissue may contribute to RA pathogenesis (51)(52)(53)(54)(55)(56)(57)(58). Marrow adipose tissue was present adjacent to the talocrural joint, and in the inter-trabecular spaces of Ctrl rats.…”
Section: Aa Depleted Extra-articular and Marrow Adipocytes; No Sparing By Sh1293mentioning
confidence: 96%
See 1 more Smart Citation
“…Adipose tissue may contribute to RA pathogenesis (51)(52)(53)(54)(55)(56)(57)(58). Marrow adipose tissue was present adjacent to the talocrural joint, and in the inter-trabecular spaces of Ctrl rats.…”
Section: Aa Depleted Extra-articular and Marrow Adipocytes; No Sparing By Sh1293mentioning
confidence: 96%
“…Bone marrow dendritic cells exposed to a b 2 -agonist can also promote Th2/Th17 cell expansion, whose activity is also influenced by marrow adipocytes (57). Moreover, the b 2antagonist, propranolol can promote trabecular bone formation in mice by regulating adipocyte metabolism (58).…”
Section: Aa Depleted Extra-articular and Marrow Adipocytes; No Sparing By Sh1293mentioning
confidence: 99%
“…More recent studies, however, showed that thermoneutral (32°C) housing in C57BL/6J mice exerted a protective effect on the skeleton, which was associated with reduced expression of Ucp1 in BAT [ 1 , 8 ]. Interestingly, the non-selective β-blocker propranolol was recently shown to be protective against adipose tissue loss, but only partly protective against bone loss, in mice housed at room temperature compared to thermoneutrality [ 9 ]. It is clear that cold temperature influences bone and marrow adipose tissue, but what particular afferent thermoregulatory pathways may be involved in these processes is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Group housing attenuates the increase in non-shivering thermogenesis in BAT in mice exposed to a cool environment 11 but it is plausible that another aspect of the spaceflight environment increases sympathetic signaling, an important positive regulator of thermogenesis. Whatever the precise mechanism, increased thermogenesis is important because it influences multiple physiological processes [12][13][14][15] . Collateral changes associated with increased thermogenesis include cancellous bone loss, immune suppression, increases in glucocorticoid production, increases in blood pressure and heart rate, and altered tumor and tissue response to ionizing radiation [16][17][18] .…”
mentioning
confidence: 99%
“…Collateral changes associated with increased thermogenesis include cancellous bone loss, immune suppression, increases in glucocorticoid production, increases in blood pressure and heart rate, and altered tumor and tissue response to ionizing radiation [16][17][18] . Mechanistically, at least some of these responses are mediated by increased sympathetic outflow 14,19,20 .…”
mentioning
confidence: 99%